Kompetensi Guru Pendidikan Jasmani, Olahraga dan Kesehatan di Sekolah Dasar Negeri Sekecamatan Luas, Kabupaten Kaur, Provinsi Bengkulu - Roni Syaputra (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2020)
This type of research is mixed method (quantitative-qualitative) by using sequential explanatory design or combination model research. The population in this study is all teachers of physical education, sports and health in public schools sekecamatan wide. The sampling technique used a saturated sampling technique with a sample size of 7 people and an informant consisting of supervisors, principals, physical education teachers, sports and health, teachers and students. Data analysis techniques that researchers use in the early stages are (quantitative method) with Likert scale. Then in the second stage is (qualitative method) deangan component analysis data flow model.The results showed that most of the competence of teachers of Physical Education, Sport and Health at State Elementary School Sekecamatan Luas, Kaur district, Bengkulu Province included in very good category with percentage (96.49%) this shows that most teachers of Physical Education, Sports And Health at State Elementary School of Sekecamatan Luas have been able to carry out 4 main tasks of teachers with details in every aspect that is: 1) Pedagogic competence with percentage (82.29%) including very good category in understanding the learners more deeply, designing, implementing and evaluating Learning and developing the potential of learners, 2) Personality competence with percentage (87.86%) including the category of excellent in acting in accordance with religious, legal, social norms, displaying themselves as an honest person, noble, steady, stable, Wise and authoritative, 3) Social competence with percentage (93.33%) is categorized as excellent in being inclusive, acting objectively, communicating effectively, empathetically and courteously with fellow educators, education personnel, parents and society, (4) Professional competence with percentage (77.52%) including good category in mastering learning materials widely And deep. Keywords : Teacher Competence Physical Education, Sport And Health